Prognostic Impact of Sarcopenia and Radiotherapy in Patients With Advanced Gastric Cancer Treated With Anti-PD-1 Antibody - Kim, Nalee; Yu, Jeong Il; Lim, Do Hoon; Lee, Jeeyun; Kim, Seung Tae; Hong, Jung Yong; Kang, Won Ki; Jeong, Woo Kyoung; Kim, Kyoung-Mee (Frontiers in Immunology, 2021)
Background: We explored the combined effects of sarcopenia (SAR) and radiotherapy (RT) on outcomes in patients with advanced gastric cancer (AGC) treated with immune-checkpoint blockade (ICB). Methods: Among 185 patients with AGC treated with ICB, we defined SAR as skeletal muscle index <49 cm2/m2 for men and <31 cm2/m2 for women; 93 patients met criteria. We defined high neutrophil-to-lymphocyte ratio (hNLR) as NLR≥3. Palliative RT was performed in 37 patients (20%) before ICB. Results: We frequently observed hNLR in patients with SAR (53% vs. 35%, p = 0.02). The median overall survival (OS) for the entire cohort was 5 months. Stratification by risk factors of SAR or hNLR revealed a significant difference in median OS (0 [N = 60] vs. 1 [N = 76] vs. 2 [N = 49]: 7.6 vs. 6.4 vs. 2.2 months, p < 0.001). Patients with microsatellite instability-high (MSI-H, N = 19) or Epstein-Barr virus (EBV)-positive tumors (N = 13) showed favorable outcomes compared to those with microsatellite stable (MSS, N = 142) tumors (median OS, not reached vs. 16.8 vs. 3.8 months, respectively). The benefit of RT was evident in patients with both SAR and hNLR (median OS, 3.1 vs. 1.3 months, p = 0.02) and MSS/EBV-negative tumor (median OS, 6.5 vs. 3.5 months, p = 0.03), but outcomes after RT in MSI-H tumor were not significantly different. In multivariable analysis, SAR/hNLR, molecular subtypes, and a history of RT were associated with OS (all p < 0.05). Conclusions: We demonstrated the negative predictive value of SAR/hNLR on outcomes after ICB for AGC, and the history of RT could overcome the negative impact of SAR/hNLR and the MSS/EBV-negative subtype.